Terrestrial and aquatic mammals of the Pantanal - Alho,CJR. (2011)
Different works have registered the number of mammal species within the natural habitats of the Pantanal based on currently known records, with species richness ranging from 89 to 152 of annotated occurrences. Our present list sums 174 species. However, at least three factors have to be emphasised to deal with recorded numbers: 1) to establish the ecotone limit between the floodplain (which is the Pantanal) and its neighbouring domain like the Cerrado, besides the existence of maps recently produced; 2) the lack of intensive surveys, especially on small mammals, rodents and marsupials; and 3) the constant taxonomic revision on bats, rodents and marsupials. Some species are very abundant - for example the capybara Hydrochoerus hydrochaeris and the crab-eating fox Cerdocyon thous, and some are rare, and others are still intrinsically rare - for example, the bush dog Speothos venaticus. Abundance of species is assumed to reflect ecological resources of the habitat. Local diversity and number of individuals of wild rodents and marsupials also rely on the offering of ecological resources and behavioural specialisation to microhabitat components. A large number of species interact with the type of the vegetation of the habitat, by means of habitat selection through active patterns of ecological behaviour, resulting on dependency on arboreal and forested habitats of the Pantanal. In addition, mammals respond to seasonal shrinking-and-expansion of habitats due to flooding regime of the Pantanal. The highest number of species is observed during the dry season, when there is a considerable expansion of terrestrial habitats, mainly seasonally flooded grassland. Major threats to mammal species are the loss and alteration of habitats due to human intervention, mainly deforestation, unsustainable agricultural and cattle-ranching practices, which convert the natural vegetation into pastures. The Pantanal still harbours about a dozen of species officially listened as in danger.